Excavations at Tel Kabri III: the 2013 to 2019 seasons - Cline, Eric H.; Ratzlaff, Alexandra; Yasʿur-Landau, Assaf (Culture and history of the ancient Near East, 2024)
"Tel Kabri was the center of a Canaanite polity during the Middle Bronze Age. Initial excavations conducted at the site from 1986 to 1993 revealed the remains of a palace dating primarily during the first half of the second millennium BCE. Excavations were resumed at the site under the co-direction of the present editors, Assaf Yasur-Landau and Eric H. Cline, beginning in 2005. This volume presents the results of the work done at Tel Kabri during the years from 2013 to 2019, focused especially on the exploration of the rooms within the Wine Storage Complex of the palace"--